Vaccine efficacy of 45 kDa outer membrane protein of escherichia coli O157:H7 in Mice Models - Oshin, Afsana Tasnim (BRAC University, 2018)
This thesis report is submitted in partial fulfillment of the requirement for the degree of M.Sc in Biotechnology, 2017.